Pempek Bo Sang (fishcake made of banana’s floral stem) / Agung Juniarto Nugroho, Jorge August Valdano Reidina, and Muhammad Firas Al Farisi - Nugroho, Agung Juniarto; Valdano Reidina, Jorge August; Al Farisi, Muhammad Firas (Universiti Teknologi MARA, Kedah, 2019)
As part of bananas, the stems are often abandoned since people commonly use the leaves, the fruit and the banana flower. Meanwhile, the banana stems contain many medicinal properties, such as, the fluid helps detoxify human body and destroys kidney stones. The stem is also very fibrous therefore it is beneficial for weight loss. Moreover, the stems also contain a lot of phosphor, calorie, Vitamin C and Carbohydrate. Considering the usefulness of the banana stems, this project aims to elevate the value of banana stem, from waste to something whose commercial value and better usefulness. Commonly, people use banana stem for soil fertilizer and medicine, in which, not all people can use it. Hence, we tried to make the stems into something more useful, consumable and familiar to people. Our product is called Pempek Bo Sang, savory fishcake which made of banana stem). Empek-empek or Pempek is one of Indonesian favorite snacks which come from Palembang, the capital city of South Sumatera, made of ground fish mixed with starch, eggs and some seasoning. However, in this product, we replace the fish with banana stem. The texture of banana stem which is soft and easy-to-mix makes the cooking process of pempek becomes easier. Considering its nutritional value, this product will give good impact to human body. In terms of its potential for commercialization, Pempek Bo Sang will result more profit compared with other empek-empek. The price for main material of Pempek Bo Sang is considered cheaper than fish which become main material for the ordinary pempek.